UPR-induced intracellular C5aR1 promotes adaptation to the hypoxic tumour microenvironment - Tatsuya Suwa; Kelly SW. Lee; Ian J. Chai; Heather O. L. Clark; David J. MacLean; Nicole Machado; Gonzalo Rodriguez-Berriguete; Lolita Singh; Geoff S. Higgins; Ester M. Hammond; Monica M. Olcina (Cell Death and Disease)
Abstract Dysregulation of the C5a-C5a receptor 1 (C5aR1) signalling axis underlies inflammation and immune-driven pathology. C5aR1 was traditionally thought to be primarily expressed on the cell membrane, although recent reports indicate the importance of intracellular C5aR1 expression for the inflammatory effector functions of various cell types. However, the mechanisms regulating C5aR1 expression and localisation remain unclear. In tumours with an immunosuppressive microenvironment, we recently found C5aR1 expression on malignant epithelial cells, highlighting potential tumour cell–specific functions. Here, we show that physical conditions of the tumour microenvironment leading to immunosuppression, induce C5aR1 expression and control its intracellular localisation. Mechanistically, we find that low oxygen (hypoxia) induces C5aR1 expression in an unfolded protein response (UPR)-dependent manner via enhanced endoplasmic reticulum stress. Furthermore, hypoxia drives endocytosis, relocating C5aR1 from the cell membrane to the intracellular compartment. By genetically and pharmacologically targeting the C5a/C5aR1 axis, we show that C5aR1 mediates cellular adaptation to hypoxia by regulating processes associated with cell fate, including autophagy and apoptosis. In line with hypoxia-induced intracellular C5aR1 pools, the most significant pharmacological effects on cell survival are observed with selective small molecule inhibitors of C5aR1 associated with high cell permeability. These results suggest that the dysregulated C5a/C5aR1 axis and the hypoxia-induced shift in C5aR1 localisation support tumour cell survival in the hypoxic tumour microenvironment and provide new insights into therapeutic strategies for targeting the C5a/C5aR1 axis in cancer.